2021
DOI: 10.18502/ijrm.v19i9.9709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human chorionic gonadotropin intrauterine injection on oocyte retrieval day on assisted reproductive techniques outcomes: An RCT

Abstract: Background: Several mediators play an important role in implantation. One of these mediators is human chorionic gonadotropin (HCG). Objective: To evaluate the effects of HCG intrauterine injection on the day of oocyte retrieval on the result of assisted reproductive techniques (ART). Materials and Methods: In this randomized clinical trial study, 126 women who were referred to Afzalipour Infertility Center between December 2018 to December 2019 undergoing in vitro fertilization/intracytoplasmic spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The results of our study were consistent with those of other studies that were done on patients who had ICSI trials in a randomized control study with 126 women, 15 (27.3 percent) of the case group and 14 (25.5 percent) of the control group experienced positive chemical pregnancy after intrauterine injection of 1000 units of HCG immediately following oocyte retrieval. The clinical or chemical pregnancy rates did not differ significantly between the groups (14) .…”
Section: Discussionmentioning
confidence: 77%
“…The results of our study were consistent with those of other studies that were done on patients who had ICSI trials in a randomized control study with 126 women, 15 (27.3 percent) of the case group and 14 (25.5 percent) of the control group experienced positive chemical pregnancy after intrauterine injection of 1000 units of HCG immediately following oocyte retrieval. The clinical or chemical pregnancy rates did not differ significantly between the groups (14) .…”
Section: Discussionmentioning
confidence: 77%
“…Two recent RCTs evaluated intrauterine administration of hCG (dosage 1000 IU and 500 IU, respectively) immediately after OPU, rather than at ET as in the other studies. The study using the higher dosage reported no benefit with regards to LBR or any other outcome, while the trial using the lower dosage reported an increased CPR (49%) compared to saline intrauterine infusion (22.9%) ( Hosseinisadat etal. , 2021 ; Torky etal.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-four papers were assessed for eligibility. Eighteen RCTs were included in the qualitative and quantitative analysis [ 10 , 11 , 15 , 16 , 17 , 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 37 , 38 , 39 , 40 , 41 ]. The baseline characteristics of the studies included are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The most recent Cochrane review includes 17 RCTs, 6 of which are conference abstracts, and concluded that women undergoing cleavage-stage transfer might benefit from intrauterine hCG [ 20 ]. Since the publication of the latter paper, another seven RCTs have been published [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. More recently, a comprehensive meta-analysis of different interventions, including intrauterine hCG during embryo transfer, concluded that intrauterine hCG could significantly increase the clinical pregnancy rate [ 29 ].…”
Section: Introductionmentioning
confidence: 99%